Depression, Anxiety, Stress, and Their Association with Hypertension Treatment Adherence in the Elderly - Susanti, Amelia; Tasalim, Rian; Syahlani, Ahmad (INDOGENIUS, 2025)
Background & Objective: Hypertension is a major health problem in the elderly and is closely linked to increased morbidity and mortality. Poor adherence to antihypertensive medication remains a challenge, particularly in developing countries. Psychological factors such as depression, anxiety, and stress may further reduce adherence. This study aimed to analyze the relationship between psychological conditions and treatment adherence among elderly hypertensive patients at the Geriatric Clinic of Ulin Regional General Hospital, Banjarmasin. Methods: A cross-sectional analytical survey was conducted from March to July 2025 involving 85 elderly patients diagnosed with hypertension. Participants were selected using purposive sampling. Adherence was measured using the Morisky Medication Adherence Scale (MMAS-8), while depression, anxiety, and stress were assessed using the Depression Anxiety Stress Scale (DASS-21). Data were analyzed using the Chi-Square test with a significance level of p < 0.05. Results: The findings showed that 50.6% of respondents experienced moderate depression, 54.1% severe anxiety, and 42.4% moderate stress. Most respondents (60%) demonstrated low adherence to antihypertensive treatment. Statistical analysis indicated a significant association between psychological conditions and adherence (p = 0.000). Conclusion: Depression, anxiety, and stress are significantly associated with poor adherence. Integrating psychological support into hypertension management may improve adherence and reduce complications in the elderly.